Inovasi Digital dalam Manajemen Sekolah: Meningkatkan Kinerja Pendidikan di Era Teknologi - Masinambow, Christo J. R.; Lengkong, Jefrry S. J.; Rotty, Viktory N. J. (Academy of Education Journal, 2025)
Digital innovation in school management is an important aspect in improving educational performance in an era of continuously developing technology. This research aims to explore the impact of implementing a digital-based management system in improving school operational efficiency and the quality of education. The problem studied is how the implementation of technology can improve various managerial aspects in education, including administrative management, learning, and communication between educators, students and parents. The research method used is qualitative research with descriptive analysis and data collection in the form of literature studies. The research results show that the use of digital innovation can increase administrative efficiency, speed up the decision-making process, and improve the quality of learning through interactive online learning platforms. However, there are challenges such as gaps in technology access and the need for ongoing training for educators. Thus, digital innovation has great potential to improve educational performance, but requires policy support, adequate infrastructure and training to maximize its benefits.